Multidecadal analysis of beach loss at the major offshore sea turtle nesting islands in the northern Arabian Gulf. (February 2021) - Maneja, Rommel H.; Miller, Jeffrey D.; Li, Wenzhao; Thomas, Rejoice; El-Askary, Hesham; Perera, Sachi; Flandez, Ace Vincent B.; Basali, Abdullajid U.; Alcaria, Joselito Francis A.; Gopalan, Jinoy; Tiwari, Surya; Al-Jedani, Mubarak; et al.
Graphical abstract: Highlights: Recorded beach loss at the offshore nesting islands from 1965 to 2017. Changes in beach width, slopes and beach profile impact suitability of the nesting sites. Decline of nesting sites reduces the long-term stability of the sea turtle population. Satellite-based imageries show the process of beach changes of offshore nesting islands. Drivers of the beach loss may include factors such as sea level rise and dust storms. Abstract: Undocumented historical losses of sea turtle nesting beaches worldwide could overestimate the successes of conservation measures and misrepresent the actual status of the sea turtle population. In addition, the suitability of many sea turtle nesting sites continues to decline even without in-depth scientific studies of the extent of losses and impacts to the population. In this study, multidecadal changes in the outlines and area of Jana and Karan islands, major sea turtle nesting sites in the Arabian Gulf, were compared using available Kodak aerographic images, USGS EROS Declassified satellite imagery, and ESRI satellite images. A decrease of 5.1% and 1.7% of the area of Jana and Karan islands, respectively, were observed between 1965 and 2017. This translated to 14, 146 m 2 of beach loss at Jana Is. and 16, 376 m 2 of beach loss at Karan Is. There was an increase of island extent for Karan Is. from 1965 to 1968 by 9098 m 2 but comparing 2017 with 1968, Karan Is. lost as much as 25, 474 m 2 or 2.6% of the island extent in 1968. The decrease in island aerial extent was attributed to loss of beach sand. The southern tips of the island lost the most significant amount of sand. There was also thinning of beach sand along the middle and northern sections that exposed the rock outcrops underneath the beach. The process of beach changes of both islands was tracked by the satellite imagery from Landsat 1, 3, 5, 7 and Sentinel-2 during 1972 to 2020. Other factors including the distribution of beach slope, sea level changes, as well as wind & current from both northward and eastward components were analyzed to show its impact on the beach changes. The loss of beach sand could potentially impact the quality and availability of nesting beach for sea turtles utilizing the islands as main nesting grounds. Drivers of beach loss at the offshore islands are discussed in the context of sea level rise, dust storms, extreme wave heights and island desertification.